Structural components of Japan's international trade - Angelina Helou (Intereconomics, 1980)
In the last issue of INTERECONOMICS Nobumitsu Kagami analysed Japan's behavioural pattern and role in the international monetary sphere. The following complementary article covers the field of the country's foreign trade.
Keywords: 330